Iranian EFL Teachers' Uses, Attitudes, Beliefs, Roles, And Pedagogical Methods About Pronunciation Power Software In English Pronunciation Instruction - Gilakjani, Abbas Pourhosein (2015)
Pronunciation Power software is one of the computer technologies for teaching English pronunciation. Iranian EFL teachers have serious problems in their pronunciation instruction such as lack of enough time, knowledge, experience, training, and suitable pronunciation materials. In this study, the researcher examined how this software helped Iranian teachers to overcome these problems and improve their pronunciation instruction. The study examined Iranian teachers' uses, attitudes, beliefs, roles, and pedagogical methods about Pronunciation Power software in teaching pronunciation.